TEACHING ENGLISH THROUGH NEWS ARTICLES AND CURRENT EVENTS - Maxmanazarova Feruza Ismoilovna; Tursunpo’latova Kamola Nodir qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The integration of authentic news media into English as a Foreign Language (EFL) curricula represents a significant shift from traditional pedagogical frameworks toward more dynamic, real-world linguistic engagement. This research explores the efficacy of news-based language learning (NBLL) by conducting a comprehensive case study of current event articles and their impact on contextual vocabulary acquisition. By analyzing the structural and lexical complexity of contemporary news, the study identifies a crucial link between high-frequency exposure to global affairs and the development of communicative competence. To validate these theoretical observations, a quantitative analysis was conducted through a survey of 17 EFL learners, which provided empirical evidence of the pedagogical benefits of this approach. The findings demonstrate a profound positive correlation between news-based instruction and student engagement, with 94.1% of participants reporting a substantial increase in learning motivation and a superior ability to retain vocabulary within its pragmatic context. Although linguistic challenges such as "fast speech" (41.2%) remain a factor in digital media consumption, the study reveals that news articles effectively overcome the limitations of static textbooks by providing an evolving linguistic environment. Ultimately, the research concludes that strategic news integration is a vital tool for fostering critical thinking and ensuring that learners are equipped with the functional language skills necessary for 21st-century global discourse.